Intravesical midurethral sling mesh erosion secondary to transvaginal mesh reconstructive surgery - Sukanda Bin Jaili; Tsia-Shu Lo; Tomy Wijaya; Pei-Ying Wu (Wolters Kluwer Medknow Publications, 2015)
Objective: We sought to evaluate the feasibility and the outcomes of correcting the intravesical mesh erosion after secondary mesh augmented pelvic reconstructive surgery pervaginally. Methods: We evaluated a case of mesh erosion following midurethral sling that occurred 4 years after secondary mesh surgery. Prior to second surgery, ultrasound and cystoscopy examination were performed to exclude mesh complication. Serial examinations during follow-up after the operation were uneventful until the patient presented 4 years after the second surgery with a history of dysuria and hematuria. Cystoscopy examination discovered intravesical mesh erosion 4 years after the secondary surgery. Removal of the midurethral sling mesh erosion and bladder repaired were done vaginally. Results: The patient was still symptom free and continent 1 year following tape excision. Urodynamic evaluation 6 months post-tape excision was also normal. Conclusion: Repeated vaginal reconstructive surgery may jeopardize a primary mesh or sling, and pose a high risk of mesh erosion, which may be delayed for several years. Removal of the mesh erosion and bladder repair are feasible pervaginally with good outcome.